Carotid sinus-acute left ventricular failure and stimulation - Alzamora Castro, V. (1956)
In hypertensive subjects-carotid sinus stimulation can lower blood pressure to normal or subnormal. The reflection shortens the fatigue of cardiac patients undergoing exercise testing. In acute left ventricular failure accompanied by hypertension-carotid sinus massage is a therapeutic procedure recommended.